Improved glycemic and weight control with Dulaglutide addition in SGLT2 inhibitor treated obese type 2 diabetic patients at high cardiovascular risk in a real-world setting. The AWARE−2 study - Cesare Berra; Roberto Manfrini; Francesco Bifari; Elisa Cipponeri; Renata Ghelardi; Lucia Centofanti; Umberto Mortola; Elena Lunati; Loredana Bucciarelli; Vincenzo Cimino; Franco Folli (Pharmacological Research)
We evaluated the effects on glycemic control and body weight of a GLP1-RA in obese type 2 diabetic patients treated with SGLT2-inhibitors and other hypoglycemic agents and/or insulin, in a real-world setting. A cohort of 583 type 2 diabetic outpatients treated with a SGLT2 inhibitor and/or other anti-diabetic medications were examined. Because patients had suboptimal glycemic control, the GLP1-RA Dulaglutide was added to ongoing medications. At 6 months, 334 patients had a follow-up visit. Patients were classified in terms of cardiovascular risk (CVR) employing the ESC-EASD 2019 criteria, with the AWARE app. The study’s primary endpoints were changes in: 1) HbA1c level, 2) BMI, and 3) body weight after six months of treatment. Secondary endpoints were evaluation of Dulaglutide addition in type 2 diabetic patients: 1) with more or less than ten years of T2DM; 2) more or less than 75 years of age and in different subgroups of CVR. In the 334 patients which had a 6 months follow-up visit, age was 65,9+9,8; 33.5 % (112) were females and 66.5 % (222) were males. After six months of Dulaglutide treatment, we found a significant reduction in HbA1c levels (8.0+10.5 mmol/mol; p<0.0001) and in body mass index (1.1+1.1 kg/m2; p<0.0001). Efficacy of Dulaglutide was not affected by different CVD risk categories, age and T2DM duration. This real world study provides evidence for significant reductions in HbA1c level, body mass index and body weight in obese type 2 diabetic patients who received add-on treatment with the weekly GLP-1RA, Dulaglutide.